(untitled) (Eastern Medical College Journal, 2025)
Background: The current outbreak of the coronavirus disease 2019 (COVID-19) is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). First identified in Wuhan, China, in December 2019, COVID-19 was announced a global pandemic on the 11th of March in 2020 by the World Health Organization (WHO). Pregnancy is associated with physiological changes in women which make them more susceptible to respiratory infections and subsequent rapid progression to respiratory failure. Pregnant women should be evaluated for being potential risk groups in the current COVID-19 pandemic. But the presence of COVID-19 should not affect the method of delivery unless the mother’s respiratory state needs immediate attention for giving birth. Compared to the general population, women with COVID-19 have considerably greater rates of cesarean. The objective of the study is to assess the mode of institutional delivery of mothers during COVID-19 pandemic. Materials & methods: This cross-sectional study was conducted in Comilla Medical College Hospital, Cumilla, between July 2020 to June 2021. A total of 208 mothers were included who were admitted in the inpatient department or attending the outpatient department of gynaecology and obstetrics for delivery and postnatal care. Data was collected by face-to-face interview through a pretested, semi-structured interview questionnaire. Data was analyzed by SPSS version 25. Results: Majority of the respondents (53.6 %) of this study were in 15-25 years age group. 60.1% mothers had para 1-2 and 91.3% had no history of bad obstetrical events. Among the 208 respondents, most of the respondents were Covid-19 negative (91.8%) and history of birth by caesarean section (66.3%). Conclusion: The study shows that during COVID-19 pandemic, the number of cesarean sections that were performed nearly doubled in comparison to the number from pre covid period. Eastern Med Coll J. July 2025; 10 (1): 6-12